MoS2-based absorbers with whole visible spectrum coverage and high efficiency - Hashemi, Mahdieh; Ansari, Narges; Vazayefi, Mahsa (Scientific reports, 2022)
To design highly efficient and broadband nanometer-sized absorbers based on the atomically thin transition metal dichalcogenides (TMDCs), we propose utilizing inclined gold gratings on MoS 2 monolayer. In the case of gold gratings with zero inclination, coverage of the absorption spectrum in the entire visible range occurs between the values of 42% to 73%. Considerable increase in the absorbed light occurs by introducing 13 nm inclination to the gold gratings with equal values of the grating’s period and width as 60 nm. With the application of this grating, maximum absorption of 88% is reached and the absorption bandwidth covers the entire visible spectrum with only 12% variation of the absorption value relative to this maximum (88%). Footprints of resonant excitation of two different modes in the absorber structure are evident: the named “reflection” mode and localized surface plasmons (LSPs). Inclination of the gratings leads the LSP modes to slide toward the MoS 2 and causes a remarkable increment in the absorption efficiency. An impressive absorption value of 56% in MoS 2 monolayer is gained by the gold grating’s inclination of 17 nm. The designed absorber paves a new way in designing TMDC-based absorbers with extended bandwidths and higher efficiencies.